Business Process Reengineering of CV Dext Jaya Sentosa to Support the Supply Chain Management - Bayu Setyo Nugroho; Ardhana Shofwan Firdaus; Nandaniko Pamade W; Nicky Visha Varma; Novi Rara Amiyati; Taufik - Rohman (Politeknik Negeri Semarang, 2023)
Technological advances and developments have helped many entrepreneurs to improve their businesses. Business processes that were originally carried out manually have been replaced by computerized-based automated management. One application of technology in the business world is the use of ERP software. Many companies use ERP software to integrate data between departments. One company that implements ERP software is CV Dext Jaya Sentosa. Implementation of ERP software at this company includes the process of supplying goods from vendors, recording cashiers, and managing customers. The ERP software used is Odoo with the modules used namely Purchase, Point of Sale (POS), and Customer Relationship Management (CRM). Odoo was chosen for this implementation because this software is open source and free to use but with certain conditions. The application of Odoo begins with planning the company's needs, which is then carried out by making a system design. All results of implementing Odoo in this company are then determined by comparing the activities before and after the use of this software. The application of the Purchase Management, Point of Sales, and CRM modules is able to meet the business needs of CV Dext Jaya Sentosa.